Maize Stalk Lodging: Flexural Stiffness Predicts Strength. Issue 4 (1st July 2016) - Robertson, Daniel J.; Lee, Shien Yang; Julias, Margaret; Cook, Douglas D.
Abstract : Late‐season stalk lodging in maize ( Zea mays L.) is a major agronomic problem that has far‐reaching economic ramifications. More rapid advances in lodging resistance could be achieved through development of selective breeding tools that are not confounded by environmental factors. It was hypothesized that measurements of stalk flexural stiffness (a mechanical measurement inspired by engineering beam theory) would be a stronger predictor of stalk strength than current technologies. Stalk flexural stiffness, rind penetration resistance and stalk bending strength measurements were acquired for five commercial varieties of dent corn grown at five planting densities and two locations. Correlation analyses revealed that stalk flexural stiffness predicted 81% of the variation in stalk strength, whereas rind penetration resistance only accounted for 18% of the variation in stalk strength. Strength predictions based on measurements of stalk flexural stiffness were not confounded by hybrid type, planting density, or planting location. Strength predictions based on rind penetration resistance were moderately to severely confounded by such factors. Results indicate that stalk flexural stiffness is a good predictor of stalk strength and that it may outperform rind penetration resistance as a selective breeding tool to improve lodging resistance of future varieties of maize.